Intersection of Gender, Globalization, and Religion in Local and Globalized ELT Textbooks in Iran. - Ghajarieh, Amir; Don, Zuraidah Mohd; Mozaheb, Mohammad-Amin; Ghandil, Ghazaleh (Pertanika Journal of Social Sciences & Humanities, 2023)
This paper examines gender representation in two textbook series: Solutions, published by an international publisher, and the Iran Language Institute (ILI) series, written by local writers. Evidence of gender representation is drawn from the analysis of their religious content in the narrative texts and the illustrations. The analysis of gender representation is guided by six criteria: visibility in pictures, visibility in text, firstness, character activity, occupations, and topic dominance. The findings indicate that in both textbook series, males exhibit greater visibility and dominance in relation to character and occupation. The gender representation varies significantly. These results substantiate previous investigations conducted elsewhere, highlighting the gender imbalance in textbook representation. The examination of gender representation at the intersection of religion in local textbooks also revealed that intersectionality in social sciences can further perpetuate gender bias in educational materials. These findings serve as a call to action for textbook authors and education policymakers to prioritize gender equality representation within the context of religion and globalization in language education textbooks authored by local writers. This research holds implications for language teaching approaches fostering intercultural competence, specifically in English as a lingua franca.